RE-OS, SM-ND, U-PB, AND STEPWISE LEAD LEACHING ISOTOPE SYSTEMATICS IN SHEAR-ZONE HOSTED GOLD MINERALIZATION: GENETIC TRACING AND AGE CONSTRAINTS OF CRUSTAL HYDROTHERMAL ACTIVITY - Frei R.; Nagler T.F.; Schonberg R.; Kramers J.D. (My University, 1998)
A combined Re-Os, Sm-Nd, U-Pb, and stepwise Pb leaching (PbSL) isotope study of hydrothermal (Mo-W)-bearing minerals and base metal sulfides from two adjacent shear zone hosted gold deposits (RAN, Kimberley) in the Harare-Shamva greenstone belt (Zimbabwe) constrain the timing of the mineralizing events to two periods. During an initial Late Archean event (2.60 Ga) a first molybdenite-scheelite bearing paragenesis was deposited in both shear zone systems, followed by a local reactivation of the shear systems during an Early Proterozoic (1.96 Ga) tectono-thermal overprint, during which base metal sulfides and most of the gold was (re-)deposited. While PbSL has revealed an open-system behavior of the U-Pb systematics in molybdenite and wolframite from the RAN mine, initial Archean Re-Os ages are still preserved implying that this system in these minerals was more resistant to the overprint. A similar retentivity could be shown for the Sm-Nd system in scheelite and powellite associated with the above ore minerals. Re-Os isotopic data from the Proterozoic mineralization in the Kimberley mine point to a recent gain of Re, most pronouncedly affecting Fe-rich sulfides such as pyrrhotite. A significant Re-loss in powellitic scheelite (an alteration phase of molybdenite-bearing scheelite), coupled with a marked loss of U in W-Mo ore minerals, complements the observation of a major Re uptake in Fe-sulfides during oxidizing conditions in a weathering environment. Pyrrhotite under these conditions behaves as an efficient Re-sink. Lead isotope signatures from PbSL residues of molybdenite, powellite, and quartz indicate a continental crustal source and/or contamination for the mineralizing fluid by interaction of the fluids with older sedimentary material as represented by the direct host country rocks.Our investigation reveals the potential of the Re-Os isotopic system applied to crustal hydrothermal ore minerals for genetic tracing and dating purposes. The simplified chemical separation of Re and Os from geological material used in this study, together with improvements of chemical yields, will enable high precision data to be collected rapidly on crustal material with low Os concentrations in the future.
Keywords: Proterozoic; Archean; Докембрий::Протерозой; Precambrian::Archean; Precambrian::Proterozoic; Докембрий::Архей